Annual World Bank Conference on Development in Latin America and the Caribbean, 1997 Trade, towards open regionalism:proceedings of a conference held in Montevideo, Uruguay (Washington, D.C. The World Bank, 1998)
This third Annual Bank Conference on Development in Latin America and the Caribbean (LAC) focuses on trade liberalization policy, specifically " open regionalism, " a term coined to describe the fact that 1) regionalism has gone hand in hand with unil ateral trade opening:statistics on tariff and non-tariff measures affecting imports show that protectionist policies have been dismantled in the major LAC countries during the last decade; 2) regionalism has gone hand in hand with a substantial liberalization of investment regimes:provisions, including national treatment provisions, in regional trading arrangements show that several LAC countries treat foreign direct investment on exactly the same footing as domestic investment; and 3) most LAC countries are willing to participate in building a hemispheric free-trade zone and have been active, pro-liberalization members of the World Trade Organization (WTO). Speeches emphasized the political returns from trade integration:reciprocal lock-in, alliances created among pro-reform factions, pro-integration movements across countries, civil society integration, more-likely peaceful settlements to disputes, and general advancement of harmony in the Western Hemisphere through atmospherics, through positive incentive structures, and through cross-country coalitions. Because these positive linkages are largely implicit and not unduly burdensome, they make regional integration consistent with convergence toward global trade integration.
Keywords: Economic Theory and Research; Emerging Markets; Free Trade; International Economics & Trade; Law and Development; Macroeconomics and Economic Growth; Private Sector Development; Public Sector Development; Trade Law; Trade Policy